Synthesis of an angle meter two-channel discriminator working on continuous interference signal at antenna directional diagram linear scanning - M. M. Bulash; S. V. Shaliapin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The synthesis of the algorithm and structural schemes of two-channel discriminator of the angular coordinate meter of the noise-like signal source at linear scanning of the antenna directional diagram is given.